Text Readability: A Snapshot - Rawian, Rafizah Mohd (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
Selecting suitable reading materials are taxing and challenging for many English instructors. Text readability analysis can be used to automate the process of reading material selection and also the assessment of reading ability for language learners. Readability formulas have been broadly used in determining text difficulty based on learners’ grade level. Based on mathematical calculations, a readability formula examines certain features of a text in order to provide best rough approximations as an indication of difficulty. This paper reflects some aspects and issues of readability analysis.